Different Impact Of Self SNAGS Exercise And Deep Cervical Flexor Strengthening To Pain In Forward Head Posture - Melya Rossa (NHM PRESS, 1970)
Background: Forward Head Posture is posture disturbance marked by further movement of head position caused by excessive use of laptop and hand phone in non-ergonomic position. Self SNAGS is the technique of self mobilization completed with active movement that can decrease the pain on cervical vertebra. Deep Cervical Flexor Strengthening is the exercise to strengthen neck stabilizer muscle, so it can support the neck in straight position and decrease neck pain. Objective: The objective of the study was to investigate different impact of Self SNAGS and Deep Cervical Flexor Strengthening to pain in Forward Head Posture condition. Method: The study applied quasi experimental pre test and post test two group design. The samples were 12 students taken by sample random sampling. The samples were divided into two groups; group I obtained Self SNAGS intervention conducted 3 times in a week during 4 weeks, and group II got Deep Cervical Flexor Strengthening done 3 times during 4 weeks. The study used Visual Analog Scale (VAS) to measure neck pain. Result: The test result of group I with paired sample t-test obtained p=0,007 meaning that there was impact of Self SNAGS exercise to the decrease of pain on Forward Head Posture.